2015
DOI: 10.1021/ja5126275
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Salts with π-Stacking and Hydrogen-Bonding Interactions Lead the Way to Future Energetic Materials

Abstract: Among energetic materials, there are two significant challenges facing researchers: 1) to develop ionic CHNO explosives with higher densities than their parent nonionic molecules and (2) to achieve a fine balance between high detonation performance and low sensitivity. We report a surprising energetic salt, hydroxylammonium 3-dinitromethanide-1,2,4-triazolone, that exhibits exceptional properties, viz., higher density, superior detonation performance, and improved thermal, impact, and friction stabilities, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
279
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 383 publications
(283 citation statements)
references
References 44 publications
4
279
0
Order By: Relevance
“…For instance, TNT (1), PETN (2) and FOX-7 (3) have calculated Q equal to 1.29, 1.51 and 1.20 kcal/g, respectively, despite their negative heats of formation (mentioned earlier). [31], although among the highest known for C,H,N compounds, is less than the 1.80 g/cm 3 that has been suggested as being "an essential requirement for advanced energetic materials" [39]. The low Q and ρ of 4 result in relatively poor predicted values of detonation velocity and detonation pressure, D = 7.52 km/s and P = 223 kbar [31].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, TNT (1), PETN (2) and FOX-7 (3) have calculated Q equal to 1.29, 1.51 and 1.20 kcal/g, respectively, despite their negative heats of formation (mentioned earlier). [31], although among the highest known for C,H,N compounds, is less than the 1.80 g/cm 3 that has been suggested as being "an essential requirement for advanced energetic materials" [39]. The low Q and ρ of 4 result in relatively poor predicted values of detonation velocity and detonation pressure, D = 7.52 km/s and P = 223 kbar [31].…”
mentioning
confidence: 99%
“…However they have relatively low densities (Table 5). We are not aware of any C,H,N compound that has a crystal density as high as the 1.80 g/cm 3 that has been proposed as "essential" for advanced energetic materials [39]. One of the highest C,H,N densities known is the 1.76 g/cm 3 of BTATz, 4 [31].…”
mentioning
confidence: 99%
“…This criterion is satisfied by about 22% of the molecular compounds in Figure 7 but only about 6% of the ionic ones, even though the latter were predominantly nitrogen-rich while many of the former were not. As Zhang et al have pointed out [30], the interactions between polyatomic ions are directional, reflecting the nonisotropic natures of the electrostatic potentials on their surfaces (Figures 3-6). Zhang et al argued that closer packing and higher densities could be promoted by taking advantage of interactions such as hydrogen bonding, and drew attention to the hydroxylammonium ion, H3N-OH + , as being effective for this purpose.…”
Section: Crystal Densities and Electrostatic Potentialsmentioning
confidence: 91%
“…The comparison shows clearly that nitrogen-rich salts do not represent an assured path to high densities. It has been suggested that a density greater than 1.80 g/cm 3 is "an essential requirement for advanced energetic materials" [30]. This criterion is satisfied by about 22% of the molecular compounds in Figure 7 but only about 6% of the ionic ones, even though the latter were predominantly nitrogen-rich while many of the former were not.…”
Section: Crystal Densities and Electrostatic Potentialsmentioning
confidence: 98%
See 1 more Smart Citation